Efficiency of charcoal as supporting growth material in Pleurotus Ostreatus Mushroom Cultivation on various agricultural wastes mixed with rubber tree sawdust (SR) (in-Press) - Fathie, Ahmad Zakila; Mohd Shafiq, Mohd Sueb; Ruzinah, Isha; Siti Hajar, Kamaluddin (AIDIC Servizi, 2021)
Presently, the production of oyster mushroom in Malaysia is using rubber sawdust (SR) as the main medium to cultivate the oyster mushroom. Due to high demand and shortage of SR, other lignocellulosic wastes from oil palm wastes are used as an alternative substrate with the purpose of cultivating the oyster mushroom. This study was carried out to investigate the effect of additional charcoal as supporting growing material in the cultivation of the fungus Pleurotus ostreatus using various agricultural wastes mixed with SR. The SR, palm pressed fiber (PF), sugarcane bagasse (SB), corncob (CC) and charcoal were analyzed for their elemental compositions. The charcoal addition was varied to 0 wt%, 2 wt% and 4 wt% for 100 % SR, 50 % SR + 50 % PF, 50 % RS + 50 % SB and 50 % SR + 50 % CC substrates. It is hypothesized that the charcoal addition can boost up the yield and the mushroom quality as a growth supporting material. These substrates also have been supplemented with a fixed ratio of wheat bran and limestone to enhance the mushroom production. The number of days of mycelium growth, the number of days of pin head formation and yield for every flush were recorded. All the substrate containing charcoal, either 2 wt% or 4 wt%, showed a faster growth of mycelium rather than the substrate without the charcoal addition except for the 50 % SR + 50 % SB substrate. The 100 % SR with 2 wt% of charcoal substrate recorded the fastest mycelium growth which around 19 days. The 100 % SR, without the addition of charcoal, which acts as a control substrate, recorded the fastest pin head formation as well as fruiting body formation, around 27 d and 29 d, as compared to other substrate formulations. In terms of total average yield and biological efficiency (BE), the 50 % SR + 50 % SB without charcoal addition substrate shows the maximum average of total yield (207.96 g/bag) and the highest BE of 78.48 %. Meanwhile, the 100 % SR with 2 wt% of charcoal addition substrate produced an average total yield of 203.33 g/bag and BE of 64.55 % and these values are close to the 50 % SR + 50 % SB without charcoal addition substrate. In conclusion, the 50 % SR + 50 % SB without charcoal addition was found to be the best substrate for the cultivation of the oyster mushroom followed by 100 % SR with 2 wt% charcoal addition substrate based on the total average yield and BE. However, the other combination of the agricultural wastes and SR can be applied as an alternative substrate to cultivate the oyster mushroom since the availability of the SR is limited in Malaysia.